Context-driven migration and diffusion of pervasive services on the OSGi framework. (15th December 2009) - Preuveneers, Davy; Berbers, Yolande
The ubiquity of wireless ad hoc networks and the benefits of loosely coupled services have fostered a growing interest in service-oriented architectures for pervasive computing. Context-aware services and runtime adaptation are key to expedite human interaction with dynamic pervasive computing environments. We explore two types of live service mobility to avoid service disruptions in mobile ad hoc networks. Service migration moves a service at runtime from one host to another including its state, while service diffusion replicates the service and the state on multiple hosts. We analyse the basic requirements for service mobility and evaluate our OSGi-based implementation for service mobility with real life experiments. Our results show that the overhead of state transfer and synchronisation is limited for relatively small applications and that the delay for handing over to a replicated service in a small scale network with enforced network failures remains minimal.